2010
DOI: 10.3109/09513590903215581
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, metabolic, and endocrine parameters in response to metformin and lifestyle intervention in women with polycystic ovary syndrome: A randomized, double-blind, and placebo control trial

Abstract: The aim of this study was to evaluate the effects of metformin in addition to diet and exercise on endocrine and metabolic disturbances in women with polycystic ovary syndrome (PCOS) in a prospective, double-blind, randomized, placebo (PBO) control trial. Thirty women with insulin resistance and PCOS received lifestyle modification and 1500 mg of metformin or placebo for 4 months. Before and after treatment, body mass index, waist/hip ratio, blood pressure, hirsutism, and menstrual patterns were evaluated. Ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 34 publications
2
34
0
Order By: Relevance
“…When one of these events occurred, the investigators scheduled a blood draw for serum progesterone based on an estimation of time to the next luteal phase (Crosignani et al , 2003; Qublan et al , 2007; Palomba et al , 2008; Kuchenbecker et al , 2011; Nybacka et al , 2011). Finally, of the remaining three studies, one did not provide adequate information with which to judge the frequency of measurements (Fux Otta et al , 2010) and two did not assess ovulation until after the intervention had ended (Guzick et al , 1994; Pasquali et al , 2011) (Table 2, Column 3).…”
Section: Inconsistencies In the Methods Used To Measure Ovulatory Statusmentioning
confidence: 99%
See 3 more Smart Citations
“…When one of these events occurred, the investigators scheduled a blood draw for serum progesterone based on an estimation of time to the next luteal phase (Crosignani et al , 2003; Qublan et al , 2007; Palomba et al , 2008; Kuchenbecker et al , 2011; Nybacka et al , 2011). Finally, of the remaining three studies, one did not provide adequate information with which to judge the frequency of measurements (Fux Otta et al , 2010) and two did not assess ovulation until after the intervention had ended (Guzick et al , 1994; Pasquali et al , 2011) (Table 2, Column 3).…”
Section: Inconsistencies In the Methods Used To Measure Ovulatory Statusmentioning
confidence: 99%
“…In the interventions that assessed serum progesterone (Table 2, Column 2), ovulatory thresholds were always reported and ranged from ≥4 ng/ml (13 nmol/L) (Fux Otta et al , 2010) to ≥10 ng/ml (32 nmol/L) (Qublan et al , 2007; Palomba et al , 2008, 2010). It was difficult to discern whether these thresholds were internally validated or reflected the limits of detection of the various assays used.…”
Section: Inconsistencies In the Methods Used To Measure Ovulatory Statusmentioning
confidence: 99%
See 2 more Smart Citations
“…Otta et al [40] in a randomized, double-blind and placebo control trial compared lifestyle modiWcation and 1,500 mg of metformin or placebo for 4 months in 30 women with insulin resistance PCOS. They reported that metformin has an additive eVect to diet and exercise to improve parameters of hyperandrogenism and insulin resistance.…”
Section: Weight Loss and Lifestyle Modiwcationsmentioning
confidence: 99%